Implications of Principal's Managerial Competence on Teacher Performance at Kuttab An-Nubuwwah, Sukabumi City - Rubi Babullah; Kun Nurachadijat (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The purpose of this study was to find out the implications of the managerial competency of school principals in improving the performance of elementary school teachers. This study uses a qualitative approach. The collection of data obtained from various sources, backgrounds and various methods in this research is through mini-research and literature studies. The results of this study indicate that the competence of the principal in improving the performance of elementary school teachers, namely in planning the principal makes an annual school work plan (RKTS) which concerns 8 educational standards, provides SKP criteria (employee performance targets) at the beginning of the year as a guide for teacher assessment by the school principal, in practice organizes and involves teachers in scientific forums such as education and training (upgrading/in-service training, workshops and seminars), in the direction of the Principal supervises the education of teachers (class visit techniques, private talks, and group discussions) , as well as the efforts made by the Principal as a manager in improving performance is to build good communication with all teachers in building a productive work culture. The managerial competence of the principal at Kuttab An-Nubuwwah in improving teacher performance has been carried out in accordance with the stages of management properly. The managerial function of the Principal as one of the efforts to improve teacher performance, the implementation of the managerial functions of the Principal with an education management approach carried out by the Principal has carried out the stages of management which include planning, implementation and evaluation but in terms of management functions have not been optimized, in carry out an education management approach to the process of the Principal's managerial function.